INFLUÊNCIA DE FATORES REGIONAIS NA DIVERSIDADE E COMPOSIÇÃO DE PEIXES NO ALTO RIO PARANÁ, MATO GROSSO DO SUL - CAMPOS, Débora Gomes,; FERREIRA, Fabiane Silva,; PINHO, Henrique Ledo Lopes,; SÚAREZ, Yzel Rondon, (ANAIS DO ENIC, 2024)
-